THE INFLUENCE OF FOREST CANOPY COVER ON FRUIT-FEEDING BUTTERFLY COMMUNITIES IN THE HUU LIEN SPECIAL-USE FOREST, LANG SON PROVINCE - Van Bac, Bui; The Doi, Bui (Journal of Forestry Science and Technology, 2023)
The alteration of tropical forest structures due to human activities can have negative impacts on various organism communities. The purpose of this study was to investigate how forest canopy cover affects the species composition and community structure of fruit-feeding butterflies in the karst ecosystems of the Huu Lien special-use forest, Lang Son Province. Three forest fragments with high (>80%), medium (50-80%), and low (<50%) levels of canopy cover were examined. We collected fruit-feeding butterflies using Van Someren-Rydon traps, with 30 traps deployed evenly across the three fragments from May 2022 to March 2023, recording 27 butterfly species of 557 individuals in total. The results indicated that the forest fragment with medium canopy cover had the highest species richness and diversity of fruit-feeding butterfly communities. Although most species were found in all three forest fragments, the Nonmetric Multidimensional Scaling (NMDS) analysis significantly separated the community structures of fruit-feeding butterflies among the three fragments. The two species, Kallima incognita Nakamura & Wakahara and Stichophthalma fruhstorferi Röber, were mainly found in the forest fragment with high canopy cover and were considered as indicator species for this forest type. This study demonstrated the impact of forest canopy cover on the structure of fruit-feeding butterfly communities and emphasized the importance of forest canopy cover in conserving and maintaining insect diversity in karst ecosystems.